(untitled) (Philippines, 2008)
The objective of this book is to provide focal point on the issues of climate change, environment and natural rasources region. This also serves our preparation for engagement in various processes including the Bali Conference of Parties of the UN FCCC, as well as planning of the natural resources stream of APRN members.
Keywords: Bảo vệ môi trường,Bảo tồn tài nguyên thiên nhiên,Natural resources,Conservation of natural resources,Environmental protection,Tài nguyên thiên nhiên; Công dân tham gia,Công dân tham gia,Management,Citizen participation,Citizen participation,Citizen participation,Quản lý,Công dân tham gia